2018
DOI: 10.3390/app8101899
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Meter Spatial Resolution Phase-Sensitive Optical Time-Domain Reflectometry System Using Double Interferometers

Abstract: An improved phase-sensitive optical time-domain reflectometry (φ-OTDR) system with sub-meter spatial resolution is demonstrated. Two Michelson interferometers (MIs) with different path length differences are used in the proposed system. One is 10 m, the other is 9.2 m. Two Rayleigh backscattering phase traces with different spatial resolution are obtained by a phase generated carrier (PGC) algorithm at adjacent times. After using differencing and adaptive 2-D bilateral filtering algorithms, a 0.8-m spatial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
1
6
0
2
Order By: Relevance
“…The current consumption of DDSS interrogators is around 200 W (Peng & Chao, 2016;Feng et al, 2018;Richter et al, 2019). Discoveries at the quantum level (Cohen et al, 2015;Favero, 2015) suggest that even very small vibration levels can be detected.…”
Section: Interrogatorsmentioning
confidence: 99%
“…The current consumption of DDSS interrogators is around 200 W (Peng & Chao, 2016;Feng et al, 2018;Richter et al, 2019). Discoveries at the quantum level (Cohen et al, 2015;Favero, 2015) suggest that even very small vibration levels can be detected.…”
Section: Interrogatorsmentioning
confidence: 99%
“…However, the spatial resolution of this scheme is still limited by the MZI path difference. A year later, S. Feng et al used two Michelson interferometers with different optical path differences to obtain two RBS phase curves with different spatial resolutions through the PGC algorithm 156 . After adopting the differential and adaptive two-dimensional bilateral filtering algorithm, a spatial resolution of 0.8 m is obtained.…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…Several studies have shown that DAS systems based on phase-sensitive optical time-domain reflectometry (φ -OTDR) can achieve sub-meter spatial resolution by either sacrificing the sensitivity or using very high speed digitizers [23][24][25][26] . For instance, using 5 ns probe pulses, Masoudi et al 23 have demonstrate a DAS system with 50 cm spatial resolution albeit with a minimum detectable strain amplitude of 40 nε at 200 Hz.…”
Section: Introductionmentioning
confidence: 99%